2023
DOI: 10.21037/jtd-23-845
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracic surgery drainage is feasible and safe for acute necrotizing mediastinitis: a retrospective cohort study

Lin-Chuan Liang,
Zhi-Yu Peng,
Hua-Hang Lin
et al.

Abstract: Background Acute necrotizing mediastinitis (ANM) is a severe infection of the mediastinal loose connective tissue. Traditionally, it has been treated with thoracotomy, but video-assisted thoracic surgery (VATS) is been increasingly used in patients with this condition. This study aimed to compare the outcomes of VATS and open thoracotomy in treating ANM. Methods The medical records of patients with ANM who underwent surgery between March 2012 and April 2021 were retriev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…On a related note, Liang et al [20] reported VATS treatment of 48 patients with acute necrotizing mediastinitis (ANM), comparing them with a group of 16 patients that underwent thoracotomy. Postoperative outcomes, including chest drainage duration, length of hospital stay, blood transfusion, reoperation rate, and mortality were comparable between groups.…”
Section: Discussionmentioning
confidence: 99%
“…On a related note, Liang et al [20] reported VATS treatment of 48 patients with acute necrotizing mediastinitis (ANM), comparing them with a group of 16 patients that underwent thoracotomy. Postoperative outcomes, including chest drainage duration, length of hospital stay, blood transfusion, reoperation rate, and mortality were comparable between groups.…”
Section: Discussionmentioning
confidence: 99%